A memória na prisão: entre a massificação e a resistência - Braz, José Mauro Oliveira (2016)
This article aims to understand how the penitentiary institution can, through its dynamics, experiences and disciplinary practices, enable the balance of subjective differences from jailed people by the assimilation of living standards in terms of submission and obedience to the culture prison. As for the methodology used, the literature that aided the construction of this discussion and directed this work came from authors such as Foucault, Goffman, Thompson and Althusser directed such work. The phenomenon of “subjective massification” is present to the extent where institutions act in order to produce similar experiences in prison, turning them into traces of memories and souvenirs. Thus, the prison, like any other place of memory, conducts its incarcerated subjects according to a set of determinations established for the transmission of discipline and control. But the prison environment that acts in the pursuit of subjective standardization is based on contradictions and forces of correlations that also give way to resistance. Configuring, in that way, not only the preservation of the memory from that selected space, but also the production arrangements, or even better, a memory modality in terms of possible circumstances that require the power of the institution.